The Role of Precision Agriculture in Enhancing Horticultural Crop Yields - B. Goswami (International Journal of Trends in Horticulture, 2024)
This article explores the quantification of lithium and mapping of mineral composition in crushed lithium ore utilizing two distinct calibration techniques with Laser-Induced Breakdown Spectroscopy (LIBS). Thirty samples from a pegmatite lithium deposit were analyzed, with representative mineral samples extracted, mixed with resin, and polished into disks. These disks underwent examination via an analyzer and an integrated mineral analyzer, facilitating mineral identification. The first calibration technique used empirical mineral chemistry formulas to infer lithium concentrations, while the second established a conventional calibration curve for estimating lithium in unknown crushed materials. As the mining industry faces challenges in discovering deeper and lower-grade deposits, innovative methodologies and technologies are critical to meet the rising demand for lithium, especially for lithium-ion batteries, which accounted for 71% of global consumption in 2020. Australia’s leading role in lithium production underscores the need for efficient automated analysis methods. LIBS demonstrates the capability for real-time elemental analysis, overcoming limitations of traditional methods that struggle with direct lithium measurement. This study represents a significant advancement in tracking lithium content in pegmatite ore and optimizing mineral processing, potentially enhancing environmental management of mining-related tailings.
Keywords: •Lithium .Laser-Induced Breakdown Spectroscopy (LIBS) • Pegmatite deposits • Mineral composition • Calibration techniques • Lithium-ion batteries • Ore processing • Environmental management